2021
DOI: 10.1002/bbb.2294
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological and industrial applications of Streptomyces metabolites

Abstract: Streptomyces sp. produces clinically important bioactive compounds with anticancer, antiviral, and antibacterial properties. These compounds have important roles in various fields like agriculture, and medicine, with bio-economic benefits. Progress in genome mining has resulted in the characterization of various secondary metabolites such as lipstatin, macrolide lactones, clavulanic acid, and cholesterol oxidase. Integration of DNA sequencing with computational tools has provided information regarding the bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 220 publications
(338 reference statements)
0
11
0
1
Order By: Relevance
“…TB has been a major health problem for developing countries including Indonesia. The increasing resistance of the disease to first-and second-line drugs has demanded the need for a new search for antimycobacterial agents that could be effective, efficient, non-toxic, and cost effective [6]. Furthermore, continuing the search for new bioactive compounds is important because of the increasing number of antibiotic-resistant bacteria every year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TB has been a major health problem for developing countries including Indonesia. The increasing resistance of the disease to first-and second-line drugs has demanded the need for a new search for antimycobacterial agents that could be effective, efficient, non-toxic, and cost effective [6]. Furthermore, continuing the search for new bioactive compounds is important because of the increasing number of antibiotic-resistant bacteria every year.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics, such as chloramphenicol, rifampicin, vancomycin, avermectin, daunomycin, and clavulanic acid among others, are isolated from different Streptomyces spp. [5], [6]. Streptomyces play a relevant role in soil ecology and are also of important biotechnological interest as they produce several bioactive metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory synthesis is not the only strategy applied to obtain new and greater amounts of bioactive secondary metabolites. Streptomyces is a group of Gram-positive bacteria capable of biosynthesizing a wide range of natural compounds from different families, with different commercial applications and high economic value [16]. Doxorubicin, an antitumor antibiotic, and avermectin, used to treat parasitic worms and insect pests, are just two well-known examples.…”
Section: Contributionsmentioning
confidence: 99%
“…They first form vegetative hyphae firmly attached to the growth substrate and subsequently develop aerial hyphae, which differentiate into long-chain prespore compartments that subsequently mature into individual spores (Bush et al, 2015). Khushboo et al (2022) indicated that the growth of Streptomyces in liquid media by large scale production may reaches up to pellet formation starting by development of hyphae instead of spore formation, while formation of spores and aerial mycelium become blocked in various Streptomyces strains. Physiological conditions including pH, medium composition and the stirring speed of the reactor should be considered to regulate mycelia morphology.…”
Section: Challenges For Developing Phosphate-solubilizing Streptomyce...mentioning
confidence: 99%